Bad things happen here - Barrow, Rebecca (Margaret K. McElderry Books, 2022)
Seventeen-year-old Luca lives on Parris, an idyllic but cursed island with a history of unsolved deaths, but when Luca's sister becomes the latest victim, she is determined to find the murderer and soon comes face to face with the curse she has been running from her whole life.